The Relationship Between Childhood Emotional Abuse and Processing of Emotional Facial Expressions in Healthy Young Men: Event-Related Potential and Behavioral Evidence - Liu, Yutong; Peng, Huini; Wu, Jianhui; Duan, Hongxia (Frontiers in Psychology, 2021)
Background: Individuals exposed to childhood maltreatment present with a deficiency in emotional processing in later life. Most studies have focused mainly on childhood physical or sexual abuse; however, childhood emotional abuse, a core issue underlying different forms of childhood maltreatment, has received relatively little attention. The current study explored whether childhood emotional abuse is related with the impaired processing of emotional facial expressions in healthy young men. Methods: The emotional facial processing was investigated in a classical gender discrimination task while the event-related potentials (ERPs) data were collected. Childhood emotional abuse was assessed by a childhood trauma questionnaire among 60 healthy young males. The relationship between the score of emotional abuse and the behavioral as well as the ERP index of emotional facial expression (angry, disgust, happy) were explored. Results: Participants with higher severity of childhood emotional abuse responded faster on the behavioral level and had smaller P2 amplitude on the neural level when processing disgust faces compared to neutral faces. Discussion: Individuals who experienced a higher level of emotional abuse during childhood may quickly identify negative faces with less attentional resources consumed, suggesting altered processing of emotional facial expressions in young males with a history of childhood emotional abuse